Colonial and mythical mimesis in Colacho Hermanos o Presidentes de América by César Vallejo - Yangali Vargas, Jorge Luis (2018)
In the present essay we analyzed the mimetic logical in the dramaturgy by César Vallejo. It is an approach to the most emblematic of his theater play: Colacho Hermanos. Structurally, first the dramatis personae of this piece is approached and the features of the two main characters of it are pointed out: the brothers Mordel y Acidal. Then, we work on the senses that acquire the mimesis, mythical and colonial, in which the characters are involved. Finally, already it located in the colonial mimetic logic of power, the idea is analyzed with which Vallejos ́s play ends: farce finishes. Colonial mimesis, which from the Vallejo perspective characterized the Latin American political class servile to the empire. Key Words: Vallejo, Colacho Hermanos, mimesis, coloniality, myths.